2016
DOI: 10.1111/epi.13375
|View full text |Cite
|
Sign up to set email alerts
|

Termination of seizure clusters is related to the duration of focal seizures

Abstract: SUMMARYObjective: Clustered seizures are characterized by shorter than usual interseizure intervals and pose increased morbidity risk. This study examines the characteristics of seizures that cluster, with special attention to the final seizure in a cluster. Methods: This is a retrospective analysis of long-term inpatient monitoring data from the EPILEPSIAE project. Patients underwent presurgical evaluation from 2002 to 2009. Seizure clusters were defined by the occurrence of at least two consecutive seizures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
38
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 31 publications
1
38
1
Order By: Relevance
“…Ferastraoaru et al 4 reported that the duration of the last seizure within a cluster was longer, which suggested that a long seizure may be required to terminate ictal activity. We did not observe any significant difference between the last seizures in the burst compared to previous seizures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ferastraoaru et al 4 reported that the duration of the last seizure within a cluster was longer, which suggested that a long seizure may be required to terminate ictal activity. We did not observe any significant difference between the last seizures in the burst compared to previous seizures.…”
Section: Discussionmentioning
confidence: 99%
“…A fundamental question is whether consecutive seizures occurring over a short window reflect a single epileptic process or multiple distinct events. One hypothesis is that multiple seizures occur when postictal inhibitory mechanisms do not prevail over the capacity for seizures to self‐trigger . In addition, it has also been suggested that there are seizure‐induced alterations that increase excitability, thereby promoting secondary attacks .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There were no previous studies in which all AEDs were discontinued before the VEEG admission. Interestingly, we and a number of other authors observed no complications related to discontinuation or dose reduction of AEDs [2,9,10,18,19,[21][22][23][24][25]. However, it is too early to conclude that we can discontinue all AEDs from our single series of VEEG monitoring.…”
Section: Discussionmentioning
confidence: 47%
“…Capturing one seizure may be enough to rule out non-epileptic seizures or to make a diagnosis of epilepsy, but is not regarded sufficient for presurgical evaluation. Many researchers have recommended that at least three seizures are required to properly locate the epileptic region [8,9,14,17,18]. Therefore, we investigated the times of occurrence of the first seizure and third seizure.…”
Section: Discussionmentioning
confidence: 99%